دور الصيرفة الإسلامية في تمويل المؤسسات الصغيرة والمتوسطة - إسماعيل, عون; محمد, تامة; خير الدين, رزاق سالم (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة إلى إبراز دور صيغ التمويل الإسلامي في توفير التمويل اللازم للمؤسسات الصغيرة والمتوسطة،بصفتها أحد الأطراف المساهمة في إنشائها وتطويرها، ومن أجل ذلك حاولنا في الجزء النظري تقديم المفاهيم المتعلقة بالموضوع، أما الجزء التطبيقي فتمثل في دراسة ميدانية لمعرفة مساهمة بنك البركة الجزائري وكالة الوادي في تمويل المؤسسات الصغيرة والمتوسطة. حيث تمّ التوصّل من خلال هذه الدراسة إلى أنّ صيغ التمويل الإسلامي جدُّ فعّالة في تطوير وتحسين وتنمية المؤسّسات الصغيرة والمتوسطة، كما تمّ التوصّل إلى أن بنك البركة وكالة الوادي يموّل المؤسّسات الصّغيرة والمتوسطة بثلاث صيغ وهي : المرابحة، الإجارة، السلم، وهذه الصيغ تجنب البنك المخاطرة ويمنح تمويلات مضمونة وبالتالي تكون مساهمته محدودة رغم تطورها، كما أن هذه الصيغ التمويلية رغم تكلفتها العالية إلّا أنها ذات مخاطر أقل بالنسبة لهذا النوع من المؤسّسات، وبالتالي يمكن أن تكون بديلا تمويليا مناسب لها." "This study aims to showing the role of Islamic financing formulas in providing the necessary financing for small and medium enterprises, as one of the parties contributing to its establishment and development, and for this we tried in the theoretical part to present the concepts related to the subject, while the practical part it was represented in a field study to know the contribution of the Algerian Al Baraka Bank -El oued Agency in financing small and medium enterprises. Where it was concluded through this study that the Islamic financing formulas are very effective in developing, improving and developing small and medium enterprises, and it was also concluded that Al Baraka Bank-El oued Agency, finances small and medium enterprises in three forms: Murabaha, Ijarah, Salam, and these formulas avoid the bank risk and grant Guaranteed financing, and therefore its contribution is limited despite its development, and these financing formulas, despite their high cost, have lower risks for this type of institution, and therefore can be a suitable financing alternative for them."
Keywords: مؤسّسات صغيرة ومتوسطة، تمويل إسلامي، بنك البركة; small and medium enterprises, Islamic finance, Al Baraka Bank